Decision Support System for Selecting the Best Graduates of Undergraduate Students Using the Analytical Hierarchy Process (AHP) Method - Telaumbanua, Lucius Yupiter; Siregar, Realdo Alfonsius (International Journal of Informatics and Data Science, 2025)
The selection of top graduates is a crucial process in higher education, aiming to reward students who demonstrate the best performance during their studies. However, in practice, this process often only considers academic grades such as the Grade Point Average (GPA), without considering other factors such as organizational activity, non-academic achievements, or student attitudes and ethics. This can lead to unfairness and subjectivity in decision-making. This study aims to develop a Decision Support System (DSS) to assist the selection process of top undergraduate graduates objectively and measurably using the Analytical Hierarchy Process (AHP) method. AHP is used to determine the weight of each criterion based on its relative importance through pairwise comparisons. The criteria used include GPA, academic and non-academic achievements, organizational activity, and student behavior. This system provides a final result in the form of a graduate ranking based on the highest score. Test results indicate that the system is able to improve accuracy and transparency in the selection process of top graduates. This research is expected to become an information technology solution that supports fair and data-based decision-making in higher education.